A critical review of Ginger’s (Zingiber officinale) antioxidant, anti-inflammatory, and immunomodulatory activities - Ayustaningwarno, Fitriyono; Anjani, Gemala; Ayu, Azzahra Mutiara; Fogliano, Vincenzo (Frontiers in Nutrition, 2024)
Ginger (Zingiber officinale) is a rhizome that has been used as a healthy herbal plant for years. Ginger's chemical components are recognized to provide beneficial health effects, namely as antioxidants and anti-inflammatory agents with the potential to operate as immunomodulators. This literature review covers numerous publications concerning ginger's immunomodulatory potential, associated with antioxidant and anti-inflammatory effects in modifying the body's immune system. Pathophysiology of oxidative stress and inflammation were introduced before diving deep down into the herbal plants as an immunomodulator. Ginger's antioxidant and anti-inflammatory properties are provided by gingerol, shogaols, paradol, and zingerone. Ginger's antioxidant mechanism is linked to Nrf2 signaling pathway activation. Its anti-inflammatory mechanism is linked to Akt inhibition and NF-KB activation, triggering the release of anti-inflammatory cytokines while reducing proinflammatory cytokines. Ginger consumption as food and drink was also explored. Overall, ginger and its active components have been shown to have strong antioxidant properties and the potential to reduce inflammation. Challenges and future prospects of ginger are also elaborated for future development. Future collaborations between researchers from various fields, including chemists, biologists, clinicians, pharmacists, and the food industry, are required further to investigate the effect of ginger on human immunity. Collaboration between researchers and industry can help accelerate the advancement of ginger applications. * Ash 6.33 * Carbohydrate 67.81 * Energy (Kcal) 319.74 * Macro minerals (g/kg) ** P 3.81 ** K 33.84 ** Na 0.71 ** Ca 1.80 ** Mg 2.24 ** Micro minerals (g/kg) ** Fe 0.230 ** Zn 0.037 ** Mn 0.068 ** Phenolic Gingerol (%) 23-35 *** Shogaol (%) 18-25 *** Terpenoids Curcumene (%) 4.71 **** Camphene (%) 3.02 **** Zingiberene (%) 39.01 **** Zingeberon (%) 1.20 **** Ref. *[20], **[21], ***[22], ****[23] 3.1.1 Elephant Ginger (Zingiber officinale var. officinarum)Elephant ginger is commonly utilized in culinary applications and herbal beverages due to its large rhizome, a milder odor and a relatively lower fiber content and concentration of essential oil Formatted: Font: (Default) Times New Roman